Coping with climate change: The role of climate related stressors in affecting the mental health of young people in Mexico. - Jessie Pinchoff; Ricardo Regules; Ana C Gomez-Ugarte; Tara F Abularrage; Ietza Bojorquez-Chapela (Public Library of Science (PLoS), 2023)
Young people today are predicted to experience more climate change related stressors and harms than the previous generation, yet they are often excluded from climate research, policy, and advocacy. Increasingly, this exposure is associated with experience of common mental health disorders (CMD). The VoCes-19 study collected surveys from 168,407 young people across Mexico (ages 15-24 years) through an innovative online platform, collecting information on various characteristics including CMD and experience of recent climate harms. Logistic regression models were fit to explore characteristics associated with CMD. Structural equation models were fit to explore pathways between exposure, feeling of concern about climate change, and a sense of agency (meaning the respondent felt they could help address the climate crisis) and how these relate to CMD. Of the respondents, 42% (n = 50,682) were categorized as experiencing CMD, higher among those who experienced a climate stressor (51%, n = 4,808) vs those not experiencing climate stressors (41%, n = 43,872). Adjusting for key demographic characteristics, exposure to any climate event increased the odds of CMD by 50% (Odd Ratio = 1.57; 95% Confidence Interval (CI) 1.49, 1.64), highest for heatwaves. Specific climate impacts such as housing damage, loss of or inability to work, damage to family business, leaving school and physical health affected were adversely related to CMD, though for different climate hazards. More concern and less agency were related to CMD through different pathways, particularly for those exposed to recent events. Future research regarding the cumulative exposures to climate change, not just acute events but as an ongoing crisis, and various pathways that influence the mental health and well-being of young people must be clearly understood to develop programs and policies to protect the next generation.